ECONOMIC AND LEGAL ASPECTS OF ENSURING THE SOCIO-ECONOMIC SECURITY OF ENTERPRISES IN THE CONTEXT OF THE INTRODUCTION OF SOCIAL RESPONSIBILITY AND PR COMMUNICATIONS - Марія Бліхар; Галина Лук'янова; Ольга Скочиляс-Павлів; Мар'яна Повалена; Марія Вінічук (Фінансово-кредитна діяльність: проблеми теорії та практики, 2025)
The purpose of this article is to analyze the specifics and problems of economic and legal regulation of the processes of ensuring the socio-economic stability of enterprises in Ukraine in the context of current challenges and threats and also to determine the impact of corporate social responsibility of business and PR communications on this process. The results of the study give grounds to assert that there are significant problems in ensuring the socio-economic security of enterprises in Ukraine, which have been significantly aggravated by the challenges and dangers of the war of the russian federation against Ukraine. The author establishes that the level of socio-economic security of enterprises is decreasing due to large-scale destruction and the inability to carry out financial and economic activities in the territories where active hostilities are taking place and in the frontline zone, due to a significant shortage of labour resources and highly qualified workers, due to an increased tax burden on business entities, as well as due to difficulties in ensuring social protection of employees and proper working conditions. The article reveals the lack of proper mechanisms for economic influence and legal control of problems of ensuring the socio-economic security of enterprises and a systematized regulatory mechanism for its strengthening in the context of the growing influence of war factors. The necessity of forming an effective mechanism for ensuring the socio-economic security of enterprises in Ukraine is proved and one of the important tools for its implementation should be corporate social responsibility of business and PR communications. The main strategic directions of ensuring the socio-economic security of enterprises in Ukraine in the context of the challenges and dangers of our time and intensification of the processes of introducing socially oriented corporate policy of business and PR-communications are proposed, the implementation of which is advisable in such areas as: (1) environmental protection; (2) balancing the domestic labour market and resolving employment problems; (3) development of labour relations.